Designing Food Safety Management and Halal Assurance Systems in Mozzarella Cheese Production for Small-Medium Food Industry - Putri, Nilda Tri; Kharisman, Arif; Arief, Ikhwan; Abdul Talib, Hayati Habibah; Jamaludin, Khairur Rijal; Ismail, Elsayed Ali (Indonesian Journal of Halal Research, 2022)
Indonesia's small and medium-sized enterprises (SMEs) are having difficulty implementing a food safety management and halal assurance system. This article aims to design a food safety and halal assurance system for Dairy Farm SMEs. This research designed a food system by identifying the application of Good Manufacturing Practices (GMP) and the HACCP to Dairy Farm SMEs based on the survey, in-depth interviews, and document standard review. The food safety system was implemented using HACCP, and six Critical Control Point (CCP) processes were identified, including milking (raw material), storage, pasteurization, curd filtering, and cheese packaging. The halal assurance system is implemented at Dairy Farm SMEs by identifying and improving the company's business processes and the mozzarella cheese production process. In addition, a Standard Operating Procedure (SOP) was developed, including a food safety system and a halal assurance system. The research results can be used wisely by Dairy Farm SMEs to assist in obtaining recommendations from the Food and Drug Supervisory Agency and halal certification.